Competitive Cr3+ occupation in persistent phosphors toward tunable traps distribution for dynamic anti‐counterfeiting. Issue 10 (31st May 2021) - Zhang, Mengya; Wang, Zhijun; Wang, Xuejiao; Suo, Hao; Cao, Lingwei; Yao, Yao; Zheng, Mingjie; Cui, Jia; Yang, Zhibin; Li, Panlai
Abstract: Red/near infrared (NIR) long persistent phosphors have received extensive attentions in biomedical, food inspection, iris recognition, biological imaging, etc. Herein, a new phosphor, Li2 ZnGe3 O8 :Cr 3+, is reported with deep red persistent luminescence peaking at 708 nm. By adjusting the Cr 3+ doping concentration, the competitive site occupation at [ZnO6] and [GeO6] polyhedral enables different traps behaviors including trap types, trap concentration and trap depth, which in turn leads to different afterglow duration time from 2 to 20 h. The persistent luminescence mechanisms originated from different trap models have been discussed, and it is found that they can cooperate or inhibit each other, enabling different luminescence depending on time. The dynamic anti‐counterfeiting applications have been demonstrated, which provides a new way to rationally designing for multi‐functional luminescent materials.